Preventing and controlling zinc deficiency across the life course: A call to action - Lowe, Nicola M.; Hall, Andrew G.; Broadley, Martin R.; Foley, Jennifer; Boy, Erick; Bhutta, Zulfiqar A. (Elsevier, 2024)
Through diverse roles, zinc determines a greater number of critical life functions than any other single micronutrient. Beyond the well-recognized importance of zinc for child growth and resistance to infections, zinc has numerous specific roles covering the regulation of glucose metabolism, and growing evidence links zinc deficiency with increased risk of diabetes and cardiometabolic disorders. Zinc nutriture is thus vitally important to health across the life course. Zinc deficiency is also one of the most common forms of micronutrient malnutrition globally. A clearer estimate of the burden of health disparity attributable to zinc deficiency in adulthood and later life emerges when accounting for its contribution to global elevated fasting blood glucose and related non-communicable diseases (NCDs). Yet progress attenuating its prevalence has been limited due, in part, to the lack of sensitive and specific methods to assess human zinc status. This narrative review covers recent developments in our understanding of zinc's role in health; the impact of the changing climate and global context on zinc intake; novel functional biomarkers showing promise for monitoring population-level interventions; and solutions for improving population zinc intake. It aims to spur on implementation of evidence-based interventions for preventing and controlling zinc deficiency across the life course. Increasing zinc intake and combatting global zinc deficiency requires context-specific strategies and a combination of complementary, evidence-based interventions including supplementation, food fortification, and food and agricultural solutions such as biofortification, alongside efforts to improve zinc bioavailability. Enhancing dietary zinc content and bioavailability through zinc biofortification is an inclusive nutrition solution that can benefit the most vulnerable individuals and populations affected by inadequate diets to the greatest extent.